Bioaccumulation and toxicity of perfluorobutane sulfonate (PFBS) and perfluorobutane sulfonamide (FBSA) in Eisenia fetida and Eisenia andrei - Thimo Groffen; Robin Lasters; Ge Xie; Taiyeba Tanjina; Cornelis A.M. van Gestel; Lieven Bervoets (Ecotoxicology and Environmental Safety, 2025)
The widespread use and persistence of per- and polyfluoroalkyl substances (PFAS) have raised concerns about their ecological impacts. The relative lack of toxicological data for most current-use PFAS, including short-chain compounds such as perfluorobutane sulfonate (PFBS) and precursors such as perfluorobutane sulfonamide (FBSA), is an uncertainty factor in ecological risk assessment. This study investigated the bioaccumulation and chronic toxicity (mortality, light avoidance, and change in soil granulometry as proxy of burrowing behaviour) of PFBS and FBSA in the earthworm species Eisenia fetida and Eisenia andrei in the natural standard LUFA 2.2 soil. Results showed that FBSA was more bioaccumulative (biota-to-soil accumulation factor (BSAF, minimum - maximum) of 0.191–205 kg-OC/kg-ww) and toxic than PFBS, with significant mortality (28-day LC50 10.0–10.4 mg/kg dry soil) and impaired light avoidance behaviour observed at concentrations close to the 28-day LC50 concentration. PFBS exhibited a lower bioaccumulation potential (minimum - maximum BSAF of 3.85*10−5 – 7.44 kg-OC/kg-ww) and toxicity (28-day LC50 > 1000 mg/kg dry soil). For both PFAS, BSAF values were strongly dependent on exposure concentrations, with the highest BSAF values reported at the lower, environmentally relevant, test concentrations. Species-specific differences in bioaccumulation (absolute concentrations and BSAF values) were minor, with E. andrei showing slightly higher PFBS accumulation (4.13 ± 0.979 mg/kg ww) at high (1000 mg/kg dry soil) exposure concentrations than E. fetida (2.34 ± 0.0633 mg/kg ww). Despite minor differences in soil granulometry changes among exposure treatments, no clear dose-dependent patterns nor species-specific differences were observed. Overall, our results show a high bioaccumulation potential, but low toxicity, of FBSA and PFBS at environmentally relevant concentrations.